2006
DOI: 10.1029/2005jd006983
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of ultraviolet photometry and gas‐phase titration techniques for ozone reference standards at ambient levels

Abstract: [1] Intercomparison experiments were made between two independent techniques for ozone (O 3 ) reference standards often used as the primary standards in air quality monitoring networks. These techniques include ultraviolet absorption photometry of O 3 at the 253.7-nm Hg line and gas-phase titration of O 3 with excess NO. For ultraviolet photometry, a well-designed and maintained standard reference photometer (SRP) built by the National Institute of Standards and Technology (USA) was employed. For gas-phase ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…Sediment concentrations are usually high, much higher than what is predicted from the water levels (Jurado et al 2007;Dueri et al 2008). In open oceans, sediments can be considered as a final sink, and the deep ocean is together with atmospheric degradation one of the two main sinks of POPs Lohmann et al 2006). However, even though coastal sediments are an important reservoir of POPs globally (Jonsson et al 2003), they are not a final sink of POPs.…”
Section: Cycle Of Organic Pollutants In Transitional and Coastal Watersmentioning
confidence: 98%
“…Sediment concentrations are usually high, much higher than what is predicted from the water levels (Jurado et al 2007;Dueri et al 2008). In open oceans, sediments can be considered as a final sink, and the deep ocean is together with atmospheric degradation one of the two main sinks of POPs Lohmann et al 2006). However, even though coastal sediments are an important reservoir of POPs globally (Jonsson et al 2003), they are not a final sink of POPs.…”
Section: Cycle Of Organic Pollutants In Transitional and Coastal Watersmentioning
confidence: 98%
“…A second ozone standard is gas phase titration of ozone against nitric oxide gas standards. Differences between GPT and standard UV photometry have been investigated by Tanimoto et al (2006) and Viallon et al (2006bViallon et al ( , 2016 and found to be very small (~0.3%) when the newer values of the ozone absorption cross-sections (see Section 2.2.1) are used . Thus GPT supports the proposed decrease in the ozone absorption cross-section at 253.65 nm.…”
Section: Standards For the Measurement Of Ozone In The Atmospherementioning
confidence: 99%
“…The operating principle of the laser photometer and the SRP are briefly described in this section. More details of the SRP's principle and its capabilities have been presented by Paur et al [2003]. The major changes made to obtain the laser ozone photometer, which are in its optical setup, are further described.…”
Section: Measurement Setupmentioning
confidence: 99%